Rising Demand for Healthy Foods-Anthocyanin Biofortified Colored Wheat Is a New Research Trend - Garg, Monika; Kaur, Satveer; Sharma, Anjali; Kumari, Anita; Tiwari, Vandita; Sharma, Saloni; Kapoor, Payal; Sheoran, Bhawna; Goyal, Ajay; Krishania, Meena (Frontiers in Nutrition, 2022)
Wheat is a vital and preferred energy source in many parts of the world. Its unique processing quality helps to prepare many products such as bread, biscuit, pasta, noodles, etc. In the world of rapid economic growth, food security in terms of nutritional profile began to receive more significant interest. The development of biofortified colored wheat (black, purple, and blue) adds nutritional and functional health benefits to the energy-rich wheat. Colored wheat exists in three forms, purple, blue, and black color, depending upon the types and position of the anthocyanins in wheat layers, regulated by the bHLH-MYC transcription factor. Colored wheat lines with high anthocyanin, iron, and zinc contents showed antioxidant and anti-inflammatory activity and possessed desirable product-making and commercial utilization features. The anthocyanin in colored wheat also has a broad spectrum of health implications, such as protection against metabolic syndromes like obesity, diabetes, hypertension, and dyslipidemia. The idea of developing anthocyanin-biofortified wheat shapes human beings' lifestyles as it is a staple food crop in many parts of the world. This review is a compilation of currently available information on colored wheat in the critical aspects, including biochemistry, food processing, nutrition, genetics, breeding, and its effect on human health. Market generation and consumer awareness creation are vital challenges for its exploitation as a function food on a large scale.